2017
DOI: 10.1101/197988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Females prefer cooperative males even when cooperative behavior is unobserved: evidence from the mound-building mouse,Mus spicilegus

Abstract: 10Theoretical and empirical studies in humans suggest that cooperative behaviors may act as 11 signals during mate choice. However, cooperation is not always observable by potential partners 12 before mate choice. To address whether cooperative phenotypes are preferred based on cues 13 different from cooperative behaviors per se, we designed an experimental paradigm using wild-14 born mound-building mice (Mus spicilegus), a species with biparental care. In this species, 15 females cannot observe male cooperati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 82 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Tognetti et al . (2017) found that more cooperative males are preferred regardless of whether or not they were previously observed by the females, indicating that a preference for more cooperative individuals is not necessarily indicative of indirect reciprocity. It is possible that cooperative propensity is correlated with another attractive, sexually selected trait.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tognetti et al . (2017) found that more cooperative males are preferred regardless of whether or not they were previously observed by the females, indicating that a preference for more cooperative individuals is not necessarily indicative of indirect reciprocity. It is possible that cooperative propensity is correlated with another attractive, sexually selected trait.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to consider the possibility that these seemingly more complex routes to cooperation can also be maintained in different, less cognitively demanding ways (Carter, 2014). For example, Tognetti et al (2017) suggest that cooperation may be maintained through sexual selection; if the 'cooperative phenotype' is associated with other sexually selected traits then cooperation can evolve and be maintained through its association with them. Steppe mice (Mus spicilegus) invest in cooperative mound building, which can be understood as a form of parental care (Tognetti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations